PENDIDIKAN BERBASIS KEARIFAN LOKAL: MENJAGA TRADISI DI ERA DIGITAL - Kurniawan Syah Putra, Kurniawan Syah Putra (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Local wisdom-based education is an approach that integrates cultural values, customs, and traditional knowledge into the learning process. In the digital age marked by globalisation, national education faces the challenge of preserving local cultural identity while adapting to technological advancements. Local wisdom is not merely a cultural heritage but also a tool for shaping the character and ethics of students, with values such as cooperation, tolerance, and respect for nature that are relevant to be internalised in education.This study aims to examine the urgency and strategies for implementing local wisdom in digital education. Using a qualitative method based on literature review and observation, it was found that integrating local values into the curriculum and digital learning media can strengthen students' identity and foster cultural awareness. Digitalising cultural content such as folk tales, traditional games, and local arts is an important step for preserving values amid the global flow of information.In conclusion, local wisdom-based education plays a vital role in shaping a generation that is rooted in culture yet adaptable to the progress of the times. Collaboration between schools, cultural communities, and policy makers is essential for the sustainable implementation of local wisdom-based education.